The negative consequences of overambitious curricula in developing countries - Lant Pritchett; Amanda Beatty (Center for Economic Studies and ifo Institute (CESifo), 2012)
Learning profiles, that track changes in student skills per year of schooling, often find shockingly low learning gains. Using data from three recent studies in South Asia and Africa, we show that a majority of students spend years of instruction with no progress on basics. We argue shallow learning profiles are in part the result of curricular paces moving much faster than the pace of learning. To demonstrate the consequences of a gap between the curriculum and student mastery, we construct a simple, formal model, which portrays learning as the result of a match between student skill and instructional levels, rather than the standard (if implicit) assumption that all children learn the same from the same instruction. A simulation shows that two countries with exactly the same potential learning could have massively divergent learning outcomes, just because of a gap between curricular and actual pace - and the country which goes faster has much lower cumulative learning. We also show that our simple simulation model of curricular gaps can replicate existing experimental findings, many of which are otherwise puzzling. Paradoxically, learning could go faster if curricula and teachers were to slow down.
Keywords: I21; I25; O15; 330; Lernen; Lehrplan; Zeit; Bildungsniveau; Entwicklungsländer; Südasien; Afrika